Decision rules for selecting between exponential and logistic STAR - Alvaro Escribano; Òscar Jordà (University of California, Department of Economics, 1998)
A new LM specification procedure to choose between Logistic and Exponential Smooth Transition Autoregressive (STAR) models is introduced. This procedure has better consistency and power properties than that previously available in the literature. Monte-Carlo simulations and empirical evidence are provided in support of our claims.
Keywords: 330